Impact of service quality on customer satisfaction of automated teller machine service: case study of a private commercial joint stock bank in Vietnam - Nham, Phong; Phan, Chi (Business: Theory and Practice, 2015)
One of key challenge for Vietnamese commercial banks is how to compete in the market place with commonly undifferentiated services. The aim of this study is to investigate the impact of service quality performance on customer satisfaction on ATM service in a commercial bank in Vietnam. This study applies SERVPERF framework to analyze the data collected from a questionnaire survey and found that ASSURANCE and TANGIBLES factors significantly impact on the customer satisfaction.